A Bibliometric Approach to Multimodal Interaction Research Trends - Jianan Lyu, Abdul Aziz Zalay, Nor Syazwani Binti Mat Salleh (Forest Chemicals Review, 1970)
The demand for faster, more efficient, and higher recognition of human-computer interactions, especially for critical task completion rates, highlights the importance of multimodal interactions. This paper aims to identify global trends in multimodal interactions and their most relevant research areas. A total of 401 papers published in the Scopus database from 2012 to 2021 were selected for bibliometric analysis. We refined all Scopus categories related to multimodal interaction to obtain bibliometric information. This paper provides a qualitative analysis of the first 20 cited documents. Bibliometric analysis during the study revealed the number of publications per year, the growth rate of producing and cooperating countries, and sources. The United States ranked first in paper production. Publications after 2016 focus more on “visualization,” “augmented reality.” Computer Science Lectures (Including Artificial Intelligence Sub-series Lectures and Bioinformatics Lectures) is the most representative journal in the multimodal interaction research area. Keywords such as multimodal interaction and multimodality are increasing their visibility. “Multimodal interactions,” “interactive computer systems,” and “user interface” are more likely to be used in future research on multimodal interaction.